Metabólitos secundários e teor de nutrientes em híbridos de sorgo forrageiro sob déficit hídrico - TAYNÁ LEMOS DE OLIVEIRA CUNHA (2023)
Water stress can compromise sorghum growth and production, especially if it occurs at a high intensity during the reproductive stage. The objective of this work was to evaluate three forage sorghum hybrids subjected to water deficit, to verify whether it will interfere with the nutritional quality of the plant. The experiment was carried out using a randomized block design in a 3x2 factorial scheme with four replications, with three forage sorghum hybrids and two levels of evapotranspirated water replacement (50% and 100% AET). The variables were evaluated: isoflavones daidzein (D1), daidzin (D2), genistein (G1) and genistin (G2), determination of leaf nutrients P, K, Ca, Mg, S, Mn and Zn, dry matter content (DM ), crude protein (CP), neutral detergent fiber (NDF) and mineral material (MM). Isoflavones presented different levels among the hybrids evaluated and their highest quantity was in sorghum water stress. Leaf phosphorus and potassium content and dry matter content are influenced by water deficit and forage sorghum hybrids. The Agri 002-E hybrid obtained higher averages for these variables under water stress conditions. The bromatological variables were not affected by water deficit. The hybrids Brevant SS318 and BRS 658 had a higher crude protein content. The hybrid Agri 002-E, which not only demonstrated a higher concentration of daidzein and genistin, but also revealed a more efficient response to water deficit conditions in the concentration of S and P and higher dry matter content. Furthermore, this hybrid presented higher Ca and Mg values, indicating a different efficiency in the absorption of these nutrients.